Time before return to play for the most common injuries in professional football: a 16-year follow-up of the UEFA Elite Club Injury Study - Ekstrand, J.; Krutsch, W.; Spreco, A.; van Zoest, W.; Roberts, C.; Meyer, T.; Bengtsson, H. (British Journal of Sports Medicine, 2020)
OBJECTIVES: The objective was to describe the typical duration of absence following the most common injury diagnoses in professional football. METHODS: Injuries were registered by medical staff members of football clubs participating in the Union of European Football Association Elite Club Injury Study. Duration of absence due to an injury was defined by the number of days that passed between the date of the injury occurrence and the date when the medical team allowed the player to return to full participation. In total, 22.942 injuries registered during 494 team-seasons were included in the study. RESULTS: The 31 most common injury diagnoses constituted a total of 78 % of all reported injuries. Most of these injuries were either mild (leading to a median absence of 7 days or less, 6440 cases = 42%) or moderate (median absence: 7-28 days, 56% = 8518 cases) while only few (2% = 311 cases) were severe (median absence of >28 days). The mean duration of absence from training and competition was significantly different (p < 0.05) between index injuries and re-injuries for six diagnoses (Achilles tendon pain, calf muscle injury, groin adductor pain, hamstring muscle injuries and quadriceps muscle injury) with longer absence following re-injuries for all six diagnoses CONCLUSIONS: The majority of all time loss due to injuries in professional football stems from injuries with an individual absence of up to 4 weeks. This article can provide guidelines for expected time away from training and competition for the most common injury types as well as for its realistic range.